(16x+14)-9x=

Simple and best practice solution for (16x+14)-9x= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for (16x+14)-9x= equation:


Simplifying
(16x + 14) + -9x = 0

Reorder the terms:
(14 + 16x) + -9x = 0

Remove parenthesis around (14 + 16x)
14 + 16x + -9x = 0

Combine like terms: 16x + -9x = 7x
14 + 7x = 0

Solving
14 + 7x = 0

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-14' to each side of the equation.
14 + -14 + 7x = 0 + -14

Combine like terms: 14 + -14 = 0
0 + 7x = 0 + -14
7x = 0 + -14

Combine like terms: 0 + -14 = -14
7x = -14

Divide each side by '7'.
x = -2

Simplifying
x = -2

See similar equations:

| 1x+8+9x=74-1x | | 3z-2=4 | | -4(-2x+2)=72 | | X/0.8=6 | | 4x-2(x-5)=-9+4x+13 | | 9+2(x-3)=45 | | 4x-2=4x-4+2 | | 8x-4=4x+19 | | -7(8+5x)=-266 | | 6p-9=2p+15 | | p(x)=x^4-8x^3+7x^2 | | 6y-4=y+5 | | F(x)=3(x-7)+12 | | 3x+7y=4fory | | 4x^3-2x^2+5x+1=0 | | -2t+15=3 | | X^4+x^3-11x^2+5x+30=0 | | 15q/10q | | X(x)=3(x-7)+12 | | 4x^3-2x^2+5x-1=0 | | 12x-3=36 | | 8n-7=6n+9 | | 15-u=13 | | 2x+4+3y-2=12 | | (7x-2)-x=68 | | 2-7m-6m= | | -(7-x)-(7-x)=2x+14 | | .33*x=6700 | | -1=s/3-5 | | h(t)=-16t^2+112t+10 | | ​2/1a=11 | | 8x-18=14x+24 |

Equations solver categories